Improvements to a flow reactor and catalysis on core shell nanoparticles - Tenghamn, Johan (My University, 2018)
A flow reactor is a common measurement equipment in catalysis research and works by flowing reactants into a reactor/reservoir and measuring the outgoing products. At the Langhammer lab at Chalmers University of Technology there is a flow reactor developed mainly for research in plasmonic sensing where the outgoing gas was not analysed in detail. Now when used for catalysis research there was a need for improving the detection of outgoing species. By introducing a glass pocket sample holder that encapsulates the sample we reduced dilution and improved the signal by two orders of magnitude. This improvement is presented and tested with the test reaction CO oxidation. Samples cotaining novel type of supported core shell nanoparticles with gold core, alumina shell covered with either catalytic Pd or Pt particles was then tested. By varying the shell thickness between 0 and 5 nm we studied the influence on CO oxidation by comparing activation energies. Similar trends for reactions in low CO concentrations (5 % vol CO) for both Pd and Pt samples but different trends for high CO (50 % vol CO) was obtained. XPS measurements indicates that the formation Pd oxides could be influenced by the shell thickness. A possible explanation could be an effect from Fermi level equilibration and charge transfer between the core and the catalysts but this needs to be confirmed with further measures varying for example the core material.
Keywords: Fysik; Physical Sciences